Synthesis of non-natural amino acids from N-(p-tolylsulfonyl)-alpha,beta-didehydroamino acid derivatives - Ferreira, Paula M. T. (2003)
Carbon nucleophiles, amines, and oxygen nucleophiles were treated with the methyl ester of N-(tert-butoxycarbonyl)-N-(p-tolylsulfonyl)-alpha,beta-didehydroalanine, and also with the methyl esters of N-(tert-butoxycarbonyl)-O-(p-tolylsulfinyl)-alpha,beta-didehydroserine and N-(tert-butoxycarbonyl)-beta-(1,2,4-triazol-1-yl)-alpha,beta-didehydroalanine, both of which were obtained from the former substrate. Carbon nucleophiles of the beta-dicarbonyl type gave furanic amino acids, which were converted into the corresponding pyrrole derivatives (dehydroprolines) in high yields, while use of amines allowed the synthesis of alpha,alpha-diamino acids and beta-amino-alpha,beta-didehydroamino acids. Different types of alkoxyamino acids were obtained by treatment of the above substrates with oxygen nucleophiles. The reactivities of the alpha,beta-didehydroaminobutyric and alpha,beta-didehydrophenylalanine analogues were also tested. Some of the methods developed were applied to the synthesis of cross-linked amino acids, namely didehydrolanthionine and histidino-alpha,beta-didehydroalanine derivatives.